Elevated Mortality Risk from CRKp Associated with Comorbidities: Systematic Review and Meta-Analysis - Lucas Candido Gonçalves Barbosa; José Arthur Silva e Sousa; Graziela Picciola Bordoni; Gabriel de Oliveira Barbosa; Lilian Carla Carneiro (MDPI AG, 2022)
Carbapenem-resistant Klebsiella pneumoniae has become a public health problem with therapeutic limitations and high mortality associated with comorbidities. Methods: This is a systematic review and meta-analysis with a search in PubMed, SciELO, and Lilacs. Ten articles were selected, considering cohort, case-control, and cross-sectional studies. Tests for proportions and relative risk of mortality were performed, considering a 5% threshold for significance. Statistical analyses were performe dusing Rstudio® software, version 4.0.2 of Ross Ihaka and Robert Genleman in Auckland, New Zealand. Results: Klebsiella pneumoniae, associated with chronic kidney disease, was responsible for 26%/258 deaths, chronic lung disease 28%/169, diabetes 31%/185, liver disease 15%/262, and heart disease 51%/262 deaths. Carbapenem-resistant Klebsiella pneumoniae associated with chronic kidney disease was responsible for 49%/83 deaths, with diabetes 29%/73, and with liver disease 33%/73 deaths. The risk of death from carbapenem-resistant Klebsiella pneumoniae was twice as high as the number of deaths associated with carbapenem-sensitive Klebsiella pneumoniae, RR = 2.07 (p < 0.00001). Conclusions: The present study showed an increase in mortality from carbapenem-resistant Klebsiella pneumoniae when associated with comorbidities.